Dez anos de integração do ensino técnico ao médio no Centro Paula Souza um estudo a respeito da habilitação profissional em agropecuária - Mercúrio, Bruno Michel da Costa (Editora Oficina Universitária, 2022)
The result of rigorous research, Ten Years of Integration of Technical and Secondary Education at Centro Paula Souza: a study on Professional Qualification in Agriculture, by Bruno Michel da Costa Mercurio, presents analyzes on the Professional Qualification Course in Agriculture, in the modality of Technical Education integrated to the Secondary School (ETIM), of the State Center for Technological Education Paula Souza (CEETEPS). The work brings problematizations and discussions about the historical process of development of professional education in Brazil, contemplating the main educational reforms and the expansion and reorganization of professional and technological education, which led to the constitution of integrated secondary education. The reflections carried out are mediated by the researcher's practice in Agricultural Schools and experiences lived with the Movement of Landless Rural Workers. I invite people interested in the debate on the subject of Technical Education integrated into the Middle School to read this work, as it is a significant and relevant study, especially in the current Brazilian educational scenario.